Trigonella Foenum Graecum Extract Benefits on Hematological, Biochemical and Male Reproductive System as a Complementary Therapy with Glimepiride in Treating Streptozotocin Induced Diabetic Rats - A. Elghazaly Nawal; H. Zaatout Hala; H. Radwan Eman; M. Elghazaly Mohamed; A. Elsheikha Eman (Journal of Bioinformatics And Diabetes, 2019)
Diabetes mellitus (DM) is a chronic metabolic disorder. Streptozotocin is a naturally occurring cytotoxic chemical, particularly toxic to the pancreas and insulin producing beta cells in mammals and induces diabetes. Glimepiride is a second generation sulfonylurea, used as second-line or add-on treatment options for type 2 diabetes. Fenugreek (Trigonella foenum graecum) seeds have been documented as a traditional plant treatment for diabetes. Soluble dietary fiber of Fenugreek significantly improved oral glucose tolerance in diabetic rats. It also exerts anti-diabetic effects mediated through the inhibition of carbohydrate digestion and absorption and the enhancement of peripheral insulin action. Most herbal remedies can interact with allopathic drugs resulting in altered activity and toxicity. At the same time, herbal remedies might produce the same kind of effects as the drug produce. Current published research information on herb-drug interactions is scanty. So, the aim of this study was to investigate the possible interaction between conventional drug used for the management of diabetes; (Glimepiride) and a traditional herbal remedy; Fenugreek aqueous extract in Streptozotocin induced diabetic male albino rats. In conclusion, combination therapy induces better hematological, biochemical effects and improves the oxidative stress biomarkers and antioxidant enzymes. Histological studies showed better results on some organ functions. The results emphasize the benefit of using the combination of Fenugreek seeds aqueous extracts as supportive complementary anti-diabetic therapy.
Keywords: Diabetes mellitus